Comparison of Guarantee Law Based on Islamic Law and Positive Civil Law in Indonesia - Ahmad Setiawan; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
Introduction: Guarantee law is the entire legal rule that regulates the legal relationship between the giver and the recipient of the guarantee in relation to the imposition of the guarantee to obtain a facility or credit. In general, guarantees in Islamic law (fiqh) are divided into two, namely guarantees in the form of people (personal guarantees known as dlaman or kafalah) and guarantees in the form of property (rahn). Formulation of the problem: How is the legal guarantee based on Islamic law and civil law combined in positive law in Indonesia. Methods: This study uses a juridical normative method. Research Results and Discussion: The existence of guarantees is recognized in Islamic law. For guarantees provided by other parties for obligations/achievements that must be carried out by the guarantor (debtor) to the party entitled to fulfill the obligations/achievements, it is called kafalah. Then, collateral related to objects/assets that must be given to debtors (debtors) to creditors (debtors) is called rahn. Conclusion: In the Indonesian legal system, a guarantee is categorized into a guarantee that arises because it is determined by regulations and agreements, namely general guarantees and special guarantees, material guarantees and individual rights, guarantees for movable objects (onroerende goederen) and immovable objects (onroerende). zaken), guarantee by controlling and not controlling the object. collateral related to objects/assets that must be given to debtors (debtors) to creditors (debtors) is called rahn. Conclusion: In the Indonesian legal system, a guarantee is categorized into a guarantee that arises because it is determined by regulations and agreements, namely general guarantees and special guarantees, material guarantees and individual rights, guarantees for movable objects (onroerende goederen) and immovable objects (onroerende). zaken), guarantee by controlling and not controlling the object. collateral related to objects/assets that must be given to debtors (debtors) to creditors (debtors) is called rahn. Conclusion: In the Indonesian legal system, a guarantee is categorized into a guarantee that arises because it is determined by regulations and agreements, namely general guarantees and special guarantees, material guarantees and individual rights, guarantees for movable objects (onroerende goederen) and immovable objects (onroerende). zaken), guarantee by controlling and not controlling the object.